2022
DOI: 10.1101/2022.02.23.22271065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frailty in individuals with depression, bipolar disorder and anxiety disorders: longitudinal analyses of all-cause mortality

Abstract: Background: Frailty is a medical syndrome that is strongly associated with mortality risk, and an emerging global health burden. Mental disorders are associated with reduced life expectancy and elevated levels of frailty. In this study, we examined the mortality risk associated with frailty in individuals with a lifetime history of mental disorders compared to non-psychiatric controls. Methods: The UK Biobank study recruited >500,000 adults, aged 37-73, between 2006-2010. We derived the two most common albe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Socioeconomic deprivation has been demonstrated as a risk factor for poor mental health [17,23,24]. Furthermore, Mutz et al [25]. showed that higher levels of frailty in individuals with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic deprivation has been demonstrated as a risk factor for poor mental health [17,23,24]. Furthermore, Mutz et al [25]. showed that higher levels of frailty in individuals with mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…and multiple health indicators: having a long-standing illness, disability or infirmity (yes/no), self-rated health (“poor”, “fair”, “good” or “excellent”) and overall health status (unhealthy/healthy) derived from 81 cancer and 443 non-cancer illnesses (Mutz & Lewis, 2022; Mutz et al, 2021). Next we examined associations with the frailty phenotype and frailty index (Mutz, Choudhury, Zhao, & Dregan, 2022). The frailty phenotype summarises data on weight loss, exhaustion, physical activity, walking speed and hand-grip strength.…”
Section: Methodsmentioning
confidence: 99%
“…As such, few existing frailty assessments include psychological dimensions. Nevertheless, a few mental health items, such as depression, have been used in some studies to identify psychological plus other frailty domains in the context of frailty indices (Mutz, Choudhury, Zhao, & Dregan, 2022). Incorporating psychological features under the cumulative deficit approach of frailty facilitates a more thorough evaluation of the multiple factors that may lead to an older adult being frail.…”
Section: Introductionmentioning
confidence: 99%
“…As such, few existing frailty assessments include psychological dimensions. Nevertheless, a few mental health items, such as depression, have been used in some studies to identify psychological plus other frailty domains in the context of frailty indices (Mutz, Choudhury, Zhao, & Dregan, 2022).…”
Section: Introduction (603 Words)mentioning
confidence: 99%